Perbedaan Kepribadian dan Perilaku Seks Pranikah pada Remaja yang Berpacaran dan Tidak Berpacaran di Jakarta Barat - Nurul Adiningtyas; Setiawati Intan Savitri (Universitas Mercu Buana Jakarta, 2018)
Currently, more problems are found in adolescent lives. One of its problem is the increasing rate of premarital sex behavior among teenagers. Previous studies showed that personality played an important role for teenagers’ pre-marital sex behavior. Another thing related to pre-marital sex behavior is whether individuals choose to date or not to date before marriage. Several studies that link dating behavior to pre-marital sex behavior resulted in positive and significant relationship between dating behavior and pre-marital sex. This current research aim to found out whether there’s a difference between the personality of teenagers who date and who don’t date with their pre-marital sex behavior. The population of this research is grade XI students in West Jakarta and the sample was 3582 respondents using random sampling. The scale used to measure pre-marital sex behavior is a modification of Vener and Stewart’s heterosexual activity items by Miladiyani (2008) which consists of 12 pre-marital sexual behavior starting from eye-to-eye contact up to sexual intercourse.